Dialogues between Media - Ferstl, Paul (XXI. Congress of the ICLA - Proceedings, 2021)
This book unites essays on the interplay of media or inter-arts studies, as well as papers with a focus on comics studies, further testimony to the fact that comics have truly arrived in mainstream academic discourse. "Adaptation" is a key term for the studies presented in this volume various articles discuss the adaptation of literary source texts in different target media - cinematic versions, comics adaptations, TV series, theatre, and opera.